Transmission Law of Pore Water Pressure in Granite Weathered Soil Under High Hydraulic Gradient Conditions - Qiyun Wang; Jiajun Zeng; Bingqiang Zhang; Danping Gu; Wanjun Zang; Nanxiong Xiao (Advances in Civil Engineering)
With the development and utilization of large-scale urban underground space, the interaction between groundwater and underground structures has become a research hotspot. To analyze the pore pressure transfer mechanism of granite weathered soil under high water head conditions, this article uses the consolidation differential equation of saturated soil to solve the pore pressure transfer model for specific boundary conditions. To verify the effectiveness of the theoretical model, a large-scale head loss test system was constructed to carry out seepage tests of groundwater in granite weathered soil under high water head conditions. Using the experimental results, an expression for the relationship between the permeability coefficient and hydraulic gradient of granite weathered soil was established. Finally, the influence factors in the process of pore water pressure transfer in soil were studied using the pore pressure transfer theory model. The research conclusions can be used for antifloating design and seepage field analysis of underground structures, providing a basic theoretical basis and analytical method for studying the seepage law of soil, which is of great significance for ensuring the safety of underground structures.